Assessment of treatment response in non‐alcoholic steatohepatitis using advanced magnetic resonance imaging. Issue 6 (24th January 2017) - Lin, S. C.; Heba, E.; Bettencourt, R.; Lin, G. Y.; Valasek, M. A.; Lunde, O.; Hamilton, G.; Sirlin, C. B.; Loomba, R.
Summary: Background: Magnetic resonance imaging‐derived measures of liver fat and volume are emerging as accurate, non‐invasive imaging biomarkers in non‐alcoholic steatohepatitis (NASH). Little is known about these measures in relation to histology longitudinally. Aim: To examine any relationship between MRI‐derived proton‐density fat‐fraction (PDFF), total liver volume (TLV), total liver fat index (TLFI), vs. histology in a NASH trial. Methods: This is a secondary analysis of a 24‐week randomised, double‐blind, placebo‐controlled trial of 50 patients with biopsy‐proven NASH randomised to oral ezetimibe 10 mg daily ( n = 25) vs. placebo ( n = 25). Baseline and post‐treatment anthropometrics, biochemical profiling, MRI and biopsies were obtained. Results: Baseline mean PDFF correlated strongly with TLFI (Spearman's ρ = 0.94, n = 45, P < 0.0001) and had good correlation with TLV ( ρ = 0.57, n = 45, P < 0.0001). Mean TLV correlated strongly with TLFI ( ρ = 0.78, n = 45, P < 0.0001). After 24 weeks, PDFF remained strongly correlated with TLFI ( ρ = 0.94, n = 45, P < 0.0001), maintaining good correlation with TLV ( ρ = 0.51, n = 45, P = 0.0004). TLV remained strongly correlated with TLFI ( ρ = 0.74, n = 45, P < 0.0001). Patients with Grade 1 vs. 3 steatosis had lower PDFF, TLV, and TLFI ( P < 0.0001, P = 0.0003, P < 0.0001 respectively). Regression analysis of changes in MRI‐PDFF vs. TLV indicates that 10% reduction in MRI‐PDFF predicts 257 mL reduction in TLV. Conclusions: The MRI‐PDFF and TLV strongly correlated with TLFI. Decreases in steatosis were associated with an improvement in hepatomegaly. Lower values of these measures reflect lower histologic steatosis grades. MRI‐derived measures of liver fat and volume may be used as dynamic and more responsive imaging biomarkers in a NASH trial, than histology. Abstract : Linked Content This article is linked to Mansour and McPherson, and Lin and Loomba papers. To view these articles visithttps://doi.org/10.1111/apt.14005 andhttps://doi.org/10.1111/apt.14037 .